2013
DOI: 10.1016/j.bmcl.2013.05.079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (−)-epicatechin and derivatives on nitric oxide mediated induction of mitochondrial proteins

Abstract: Impaired mitochondrial function represents an early manifestation of endothelial dysfunction and likely contributes to the development of cardiovascular diseases (CVD). The stimulation of mitochondrial function and/or biogenesis is seen as a means to improve the bioenergetic and metabolic status of cells and thus, reduce CVD. In this study we examined the capacity of the flavanol (−)-epicatechin and two novel derivatives to enhance mitochondrial function and protein levels in cultured bovine coronary artery en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
1
33
1
Order By: Relevance
“…(−)-EPI effects on ERK 1/2 and CaMKII activation were assessed in the presence or absence of the selective GPER antagonist, G15 (30). Cells were stimulated with (−)-EPI 0.1 μM for 10 min, which evokes peak effect on endothelial cell signaling as previously reported by us (24). (−)-EPI treatment led to the activation of ERK 1/2 and CaMKII as denoted by their phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(−)-EPI effects on ERK 1/2 and CaMKII activation were assessed in the presence or absence of the selective GPER antagonist, G15 (30). Cells were stimulated with (−)-EPI 0.1 μM for 10 min, which evokes peak effect on endothelial cell signaling as previously reported by us (24). (−)-EPI treatment led to the activation of ERK 1/2 and CaMKII as denoted by their phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors were present during ligand stimulation. (−)-EPI was used at 0.1 μM for 10 min based on previous studies (24). As positive controls for select experiments forskolin and the GPER agonist, G1, were used at 1 μM and 0.1 μM for 10 min, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Mice fed with epicatechin demonstrated improved exercise performance and fatigue resistance, and evidence for enhanced mitochondrial biogenesis including increased ETC proteins, mitofilin, porin, mitochondrial transcription factor A (Tfam), mitochondrial volume, and cristae abundance [79]. Studying cultured bovine coronary artery endothelial cells showed that epicatechin is capable of stimulating mitochondrial function as assessed by citrate synthase activity as well as induction of structural and oxidative phosphorylation protein levels [80]. An open label study evaluating the safety and efficacy of epicatechin in subjects with Friedreich ataxia is currently being conducted.…”
Section: Enhancing Mitochondrial Biogenesismentioning
confidence: 99%
“…NO is suspected to mediate the effects of cocoa on mitochondria. In support of this thesis, a recent study demonstrated, in vitro, that flavanols are capable to stimulate mitochondrial function and biogenesis; effects disappeared with the inhibition of eNOS (107,108).…”
Section: Putative Mechanismsmentioning
confidence: 55%